Sensory and molecular characterisation of human milk odour profiles after maternal fish oil supplementation during pregnancy and breastfeeding - Sandgruber, Stefanie; Much, Daniela; Amann-Gassner, Ulrike; Hauner, Hans; Büttner, Andrea (Food Chemistry, 2011)
The odourant profile of human milk has been proposed to be modulated by the composition of the maternal diet via the transference of specific food aromas to the milk, such that neonates are exposed to these aromas and are prepared for latter acceptance of specific diets. For that reason the aim of the present study was to investigate whether specific fish oil odour constituents translate into human milk. To achieve this goal, human sensory analyses and qualitative and quantitative instrumental determination of fish oil odourants were performed on the fish oil, as well as on human milk obtained from mothers after long-term fish oil supplementation in comparison to a control group. Sensory and analytical data showed that no statistically significant modification occurred from fish oil intervention. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Breastfeeding; Two-dimensional high resolution gas chromatography; Mass spectrometry; Olfactometry; Quantification; Fish oil; Supplementation